Degradation behavior of AlGaN-based 233 nm deep-ultraviolet light emitting diodes. (20th August 2018) - Glaab, Johannes; Ruschel, Jan; Mehnke, Frank; Lapeyrade, Mickael; Guttmann, Martin; Wernicke, Tim; Weyers, Markus; Einfeldt, Sven; Kneissl, Michael
Abstract: The degradation behavior of AlGaN multiple-quantum well (MQW) deep-ultraviolet light emitting diodes emitting near 233 nm stressed at a constant current of 100 mA over 1000 h of operation has been investigated. A strong reduction of the MQW luminescence in the first 250 h and nearly stable MQW emission power over the remaining operation time is found. Moreover, the emission powers of the MQW peak as well as the emission power of parasitic peaks centered at around 266 and 403 nm are changing in a comparable manner, indicating a common degradation process. Furthermore, the leakage current below the turn-on voltage increases with increasing operation time and the change of the emission power as a function of drive current is stronger in the low current regime compared to higher currents. All effects noted up to now show the strongest impact in the first 250 h of operation. In contrast, the emission power of an additional parasitic emission band centered around 500 nm increases continuously over time. Taken altogether these observations can be explained by the following physical degradation mechanisms: the concentration of charged point defects acting as non-radiative recombination centers in the AlGaN active region increases. In addition, the concentration of point defects acting as centers for trap-assisted radiative recombination outside the active region increases.